2018
DOI: 10.1002/hep4.1172
|View full text |Cite
|
Sign up to set email alerts
|

Liver‐enriched transcription factor expression relates to chronic hepatic failure in humans

Abstract: The mechanisms by which the liver fails in end‐stage liver disease remain elusive. Disruption of the transcription factor network in hepatocytes has been suggested to mediate terminal liver failure in animals. However, this hypothesis remains unexplored in human subjects. To study the relevance of transcription factor expression in terminal stages of chronic liver failure in humans, we analyzed the expression of liver‐enriched transcription factors (LETFs) hepatocyte nuclear factor (HNF)4α, HNF1α, forkhead box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 52 publications
1
35
1
11
Order By: Relevance
“…This result was not surprising, as the ability to discern a difference in HNF4α expression in livers from patients with degenerative disease and controls based on degree of functional decompensation required the study of a large cohort of patients. ( 5 ) However, in this study, a statistically significant difference was observed based on HNF4α location. HNF4α was detected at high levels in the cytoplasm ( P = 0.023; Fig.…”
Section: Resultscontrasting
confidence: 65%
See 3 more Smart Citations
“…This result was not surprising, as the ability to discern a difference in HNF4α expression in livers from patients with degenerative disease and controls based on degree of functional decompensation required the study of a large cohort of patients. ( 5 ) However, in this study, a statistically significant difference was observed based on HNF4α location. HNF4α was detected at high levels in the cytoplasm ( P = 0.023; Fig.…”
Section: Resultscontrasting
confidence: 65%
“…( 12 ) To assess whether this observation applies to humans, we studied liver‐enriched transcription factor expression in the livers of a large cohort of patients with decompensated liver function. ( 5 ) We found that HNF4α mRNA levels were down‐regulated and correlated with the extent of liver dysfunction based on Child‐Pugh classification. Interestingly, in those studies, nuclear localization of HNF4α was not uniform.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Top 50 transcription factors revealed major changes in liver-specific transcription factors (HNF4α, C/ EBP, EGR1, and FOXA1) ( Fig. 1d; Supplemental Table 2) (Guerquin et al 2013;Guzman-lepe et al 2018). For the top five TFs, we observed large down-regulated regulons for E2F4 and ETS1 (mainly involved in cell cycle) (Hsu and Sage 2016;Fry and Inoue 2018) with suppressed activity over time, and large up-regulated regulons for HNF4α, C/EBP, and STAT1 (mainly involved in differentiation) with increased activation over time ( Fig.…”
Section: Transcriptome Analysis Of 3d Spheroid Hepg2 Differentiationmentioning
confidence: 99%